Conferring of drought tolerance in wheat (Triticum aestivum L.) genotypes using seedling indices - Ahmed, Hafiz Ghulam Muhu-Din; Zeng, Yawen; Shah, Adnan Noor; Yar, Muhammad Majid; Ullah, Aziz; Ali, Muhammad (Frontiers in Plant Science, 2022)
Wheat is the most widely grown and consumed crop because of its economic and social benefits. In many parts of the world, this crop is important for food and feed, and its productivity is particularly vulnerable to abiotic factors. In our research, we used morphological and photosynthetic attributes to define the selection criteria for drought tolerance in bread wheat genotypes at the seedling stage. In present study 40 wheat genotypes were studied to adjudicate the drought tolerance level using a completely randomized design (CRD) in 250 ml disposable cups. The wheat germplasm was tested under normal and two drought stress level D1 (50% field capacity) and D2 (75% field capacity) for different seedling attributes like Germination Percentage (GP), Chlorophyll Content (CC), Shoot length (SL), Root length (RL), shoot fresh weight (SFW), root fresh weight (RFW), Seedling fresh weight (SDFW), Shoot dry weight, Root dry weight, Relative water content, Root/Shoot ratio, and Seedling dry weight (SDDW). Using examined traits Analysis of variance (ANOVA) and spider analysis indicate that significant amount of difference was present among studied genotypes. Correlation analysis showed that root length has a significant and positive association with root/shoot ratio, dry weight, and fresh weight while negatively correlated with shoot length (SL) and relative water content (RWC). Wheat germplasm can be improved by selection, basis on these traits. Multivariate analysis showed that out 13 principal components only five PCs are significant among all treatments and has eigenvalue > 1, cumulatively showed 82.33%, 83.07%, and 97.34% of total variation under normal, D1 and D2 conditions, respectively. Splendidly the result of spider graph and multivariate analysis showed that the genotypes G49, G63 and G67 performed well in all drought stress conditions and considered as drought tolerant genotypes. The best performing genotypes can be used in future breeding programs. Selection on the bases of studied attributes is effective for development of drought tolerant and high yielding varieties